Circular Business Models for Remanufacturing in the Electric Bicycle Industry - Koop, Carina; Grosse Erdmann, Julian; Koller, Jan; Döpper, Frank (Frontiers in Sustainability, 2021)
The rising popularity and strong increase in the number of electric bicycles make it necessary to consider the built-in resources as well as possible treatments after the use phase. The time lag between the purchase and the occurrence of relevant defects suggests significant increases in defective components. Especially the great dynamics of the market due to regular innovations, product renewals, and the lack of spare parts availability for older models make the long-term use by customers much more difficult than for conventional bicycles. Therefore, it is necessary to analyze circular business models for the electric bicycle market. In this way, the required structures for a sustainable electric bicycle industry can be created so that valuable materials do not go into disposal but undergo a new use phase. Based on the results of “AddRE-Mo - Value Preservation Scenarios for Urban Electromobility of Persons and Loads through Additive Manufacturing and Remanufacturing”, a research project funded by the German Federal Ministry of Education and Research, this paper addresses four circular business models, two sales models and two service models. The guiding research interest of this paper is the combination of remanufacturing and additive manufacturing from a business model perspective, analyzing the extent to which additive remanufacturing can be considered a solution for electric bicycles’ circularity. After describing the approach and methods used to develop these four circular business models the business models are described and analyzed using the Business Model Canvas. Based on this analysis, it is shown that the combination of remanufacturing and additive manufacturing can be applied to the electric bicycle market and be integrated into both sales and service models. The description of these business models will help managers design viable business models in the context of sustainable electric bicycles. It also shows that the individual partners within the value chain must collaborate more closely. In the electric bicycle industry, a single company will probably not be able to close the product cycle completely. Further research is needed to develop concepts of the business models and examine their practical feasibility in technical and organizational operations to achieve a circular economy.